2001
DOI: 10.1074/jbc.m009737200
|View full text |Cite
|
Sign up to set email alerts
|

Versican V1 Proteolysis in Human Aorta in Vivo Occurs at the Glu441-Ala442 Bond, a Site That Is Cleaved by Recombinant ADAMTS-1 and ADAMTS-4

Abstract: Mature human aorta contains a 70-kDa versican fragment, which reacts with a neoepitope antiserum to the C-terminal peptide sequence DPEAAE. This protein therefore appears to represent the G1 domain of versican V1 (G1-DPEAAE(441)), which has been generated in vivo by proteolytic cleavage at the Glu(441)-Ala(442) bond, within the sequence DPEAAE(441)-A(442)RRGQ. Because the equivalent aggrecan product (G1-NITEGE(341)) and brevican product (G1-EAVESE(395)) are generated by ADAMTS-mediated cleavage of the respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
428
3
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 428 publications
(454 citation statements)
references
References 47 publications
17
428
3
6
Order By: Relevance
“…Pericellular proteolysis by MMPs is essential for tumor cell invasion Stamenkovic, 1999, 2000;Sternlicht and Werb, 2001), and ADAMTS-1 has been shown to play an important role in degrading versican (Sandy et al, 2001), an important component of the ECM and blood vessel wall. We have now shown that ADAMTS-1 promotes extravasation of TA3 cells into the lung parenchyma ( Figure 5A and B).…”
Section: Adamts-1 Promotes Invasion Of Ta3 Cells Through Matrigelmentioning
confidence: 99%
See 1 more Smart Citation
“…Pericellular proteolysis by MMPs is essential for tumor cell invasion Stamenkovic, 1999, 2000;Sternlicht and Werb, 2001), and ADAMTS-1 has been shown to play an important role in degrading versican (Sandy et al, 2001), an important component of the ECM and blood vessel wall. We have now shown that ADAMTS-1 promotes extravasation of TA3 cells into the lung parenchyma ( Figure 5A and B).…”
Section: Adamts-1 Promotes Invasion Of Ta3 Cells Through Matrigelmentioning
confidence: 99%
“…Several studies have shown that ADAMTS-1 is capable of degrading aggrecan and versican, which are components of extracellular matrix (ECM) barriers Sandy et al, 2001;Russell et al, 2003). However, despite this suggestive evidence of a role for ADAMTS-1 in tumor invasion and metastasis, recent studies, characterizing the expression level of ADAMTS-1 in various cancers and its role in tumor growth and metastasis, have yielded apparently contradictory results.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] A range of ECM proteins have been identified as potential ADAMTS1 substrates, including collagens, 6 nidogen, 7 and syndecan-4 8 ; however, the proteoglycans versican and aggrecan have been consistently shown to be key ADAMTS1 targets. 4,9,10 ADAMTS1 processing of versican is important in cell migration during wound healing, 11 endothelial cell invasion, 12 and remodeling of cardiac jelly ECM during heart morphogenesis. 13 These observations indicate that ADAMTS1 mediates acute regulated tissue remodeling processes that occur in development and in adult reproductive tissues, but also in cancer growth and metastasis.…”
mentioning
confidence: 99%
“…To evaluate the odontoblast expression patterns of the versican splice variants, primer pairs were designed based upon the variable exon use in the four versican variants known from other mammals (V0 probe, exon 7-8 ; V1 probe, exon 6-8 ; V2 probe, exon 7-12 ; and V3 probe, exon [6][7][8][9][10][11][12]. The RT-PCR amplifications underwent a 5 min denaturation at 94°C followed by 30 cycles at 94°C for 30 sec, primer annealing at 55°C for 30 sec, and product elongation at 72°C for 30 sec.…”
Section: Rna Preparation and Reverse-transcription Polymerase Chain-rmentioning
confidence: 99%
“…To immunodetect versican, the samples were digested with ADAMTS4 (R & D Systems, Minneapolis, MN, USA) which can cleave the versican V0 and V1 variants in the GAG-β domain 8) . The albumin-IgG-free samples (80 μg) were dissolved with 80 μL of 50 mM TrisHCl, 10 mM CaCl 2 , 150 mM NaCl and 0.05% Brij-35 buffer (pH 7.5).…”
Section: Western Blottingmentioning
confidence: 99%